1997
DOI: 10.1161/01.cir.95.2.395
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Sensitivity in Patients With Vasovagal Syncope

Abstract: In patients with vasovagal syncope, during the application of subhypotensive LBNP, there is impaired forearm vasoconstriction or paradoxical forearm vasodilation. This suggests impaired cardiopulmonary baroreceptor inactivation or paradoxical activation of these receptors and is consistent with reduced cardiopulmonary baroreceptor sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
0
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 29 publications
8
53
0
4
Order By: Relevance
“…On contrary, TPR did not change signifi cantly by assuming an upright position in HUT positive patients (1550.1 ± 576.3 vs 1741.9 ± 738.4 dyne.s/cm 5 , p = 0.90) nor in HUT negative patients (1642.7 ± 702 vs 1783.9 ± 695.5 dyne.s/cm 5 , p = 0.37) BRS decreased signifi cantly in the fi rst 5 minutes of HUT in both group of patients (HUT positive group: 9.0 ± 4.7 vs 5.6 ± 3.0, p < 0.0001, HUT negative group 8.5 ± 5.1 vs 6.2 ± 2.8, p < 0.0001) HUT There were no signifi cant differences in hemodynamic values and BRS during passive HUT between HUT positive and HUT negative patients (Tab. 2).Similarly, no signifi cant differences between HUT positive and HUT negative group were present during early phase (0-5 minutes) of nitroglycerine-stimulated HUT (Tab.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…On contrary, TPR did not change signifi cantly by assuming an upright position in HUT positive patients (1550.1 ± 576.3 vs 1741.9 ± 738.4 dyne.s/cm 5 , p = 0.90) nor in HUT negative patients (1642.7 ± 702 vs 1783.9 ± 695.5 dyne.s/cm 5 , p = 0.37) BRS decreased signifi cantly in the fi rst 5 minutes of HUT in both group of patients (HUT positive group: 9.0 ± 4.7 vs 5.6 ± 3.0, p < 0.0001, HUT negative group 8.5 ± 5.1 vs 6.2 ± 2.8, p < 0.0001) HUT There were no signifi cant differences in hemodynamic values and BRS during passive HUT between HUT positive and HUT negative patients (Tab. 2).Similarly, no signifi cant differences between HUT positive and HUT negative group were present during early phase (0-5 minutes) of nitroglycerine-stimulated HUT (Tab.…”
Section: Resultsmentioning
confidence: 85%
“…Reduced arterial barorefl ex sensitivity was reported in patients suffering from vasovagal syncope in some studies (1,3,4), whereas another studies did not found differences in barorefl ex sensitivity in these subjects (5). In some reports, an increased baroreceptor refl ex gain was observed in fainting subjects (6, 7).…”
Section: Introductionmentioning
confidence: 97%
“…30 Additionally, diminished vascular resistance responses during orthostatic challenges have been shown in many patients with neurally mediated syncope well before the onset of syncope. 13,[31][32][33] It has also been reported that administration of midodrine (␣ 1 -agonist drug) at the end of bed rest significantly ameliorated the excessive decreases in blood pressure and presyncope during a provocative tilt test 34 and that enhancement of sympathetic tone by yohimbine (an ␣ 2 -antagonist) markedly improved orthostatic tolerance in patients with neurally mediated syncope. 35 Taken together, these results indicate that vasoconstrictor capacity may be a contributor to the individual variability in orthostatic intolerance.…”
Section: Individual Variability In Orthostatic Intolerancementioning
confidence: 95%
“…Important neural control mechanisms known to be altered in patients with syncope, such as high-and lowpressure baroreceptor reflex control of heart rate, 13,14,33 were not directly addressed.…”
Section: Limitations Of the Studymentioning
confidence: 99%